Genesis of legal regulation of relations in the sphere of commercial secrets protection - Homotiuk, Oksana; Slipchenko, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The process of formation and development of legal regulation of relations in the sphere of commercial secret protection is analyzed, proposals on the improvement of current domestic legislation in the field of commercial secret protection are substantiated, foreign experience of legal regulation of commercial secrets has been researched.